The role of meetings in strategizing - Seidl, David (Henry Stewart Talks, 2013)
Views on the role of meetings, Meetings from a practice perspective, Central aspects of meetings, Central functions of meetings, Relation between meetings and strategy, Meeting practices, Meetings as strategic episodes, Meetings as rituals, Strategy workshops, Inter-organizational workshops, Areas for future research on meetings